FRI0031 Change in functional disability in acpa-positive arthralgia patients prior to progression to inflammatory arthritis. (12th June 2018) - Pentony, P.; Twigg, S.; Nam, J.L.; Mankia, K.; Hunt, L.; Hensor, E.M.; Emery, P.
Abstract : Background: Only one study 1 has assessed functional limitation in the pre-clinical phase of rheumatoid arthritis. Finding that functional limitations already exist during the symptomatic pre-arthritis phase. It is unclear if patient reported outcomes (PROs) are associated with progression to inflammatory arthritis (IA). Objectives: To assess baseline and change in PROs in the lead up to progression to IA and its association with progression to IA. Methods: From June 2008 to August 2016, 205 CCP positive patients without clinical synovitis were observed 3 monthly for 12 months and then as clinically indicated. The end point was development of IA within 12 months. PROs including HAQ, fatigue VAS, disease activity (DA) VAS and pain VAS were recorded at each visit. Cox regression was used to assess the association of each PRO at baseline with progression, then latent growth curves (LGC) were constructed to model change in PRO over time. The LGC were added as covariates in the cox regression models to determine whether changes in PROs over 12 months were associated with progression. Results: 204 anti-CCP positive cases were included (one case excluded as had only baseline data). Of these, 50 developed IA within 12 months. Estimated mean baseline HAQ was 0.53 (Standard Error, SE 0.04) and mean increase in HAQ 0.06 per 12 months (SE 0.04). Mean baseline fatigue and pain VAS were 32 mm and 28 mm, respectively (SE 1.8 and 1.6, respectively). Mean increases in fatigue and pain per 12 months were 3.9 mm (SE 2.6) and 3.5 mm (SE 2.1), respectively. Table 1 shows how hazard ratios for progression IA relate to baseline and change in HAQ and VAS. Hazards for progression to IA were increased with greater baseline fatigue VAS, and greater rate of increase in reported functional impairment, fatigue and pain. Conclusions: Greater rates of increase in HAQ, fatigue and pain VAS were associated with small, but statistically significant increases in hazards of progression. Therefore, patient reported measures may be helpful for risk stratification in patients with positive anti-CCP. Reference: [1] ten Brinck RM vSH, Mangnus L, Burgers LE, Reijnierse M, Huizinga TW, van der Helm-van Mil AH. Functional Disability in Patients Presenting with Clinically Suspect Arthralgia and Progression to Clinical Arthritis [abstract]. Arthritis Rheumatol. 2016;68(supl 10). Acknowledgements: The authors would like to thank all the participating general practitioners and health professionals and the UK Clinical Research Network teams for the referrals from primary care to the study Disclosure of Interest: None declared